(untitled) (Journal of Analytical Oncology, 2012)
Tumor markers can provide convincing evidence for tumor angiogenesis in early-stage, so that the need for novel and effective methods which can detect tumor markers rapidly, sensitively and reliably is consequently being subjected to extensive interest. The biosensor based on imaging ellipsometry (BIE) is developed for the detection of Neuron specific enolase (NSE) as a trial and its diagnosis performance is evaluated. Anti-NSE antibody as ligand is immobilized on protein A modified silicon substrate to form NSE sensing surface. Then, NSE test is carried out with the setup of a calibration curve for clinical quantitative detection purpose. The relationship between BIE signal y (grayscale value) and NSE concentration x (ng/ml) is y=19.6 lg(x) + 70.1 and the limit of detection achieves 2 ng/ml. The specificity, reproducibility and accuracy for NSE detection with BIE are all adequate to clinical diagnosis requirements. 149 serum samples have been detected quantitatively with BIE and their results are in agreement with a commercial ELISA immunoassay.